Comprehensive mutational analysis of background mucosa in patients with Lugol‐voiding lesions. (2nd May 2021) - Akizue, Naoki; Okimoto, Kenichiro; Arai, Makoto; Hirotsu, Yosuke; Amemiya, Kenji; Oura, Hirotaka; Kaneko, Tatsuya; Tokunaga, Mamoru; Ishikawa, Kentaro; Ohta, Yuki; Taida, Takashi; Saito, Keiko; et al.
Abstract: Somatic mutations including the background mucosa in patients with Lugol‐voiding lesions (LVLs) are still not well known. The aim of this study was to evaluate the somatic mutations of the background mucosa in patients with LVLs (Squamous cell carcinoma (SCC), intraepithelial neoplasia (IN), and hyperplasia). Twenty‐five patients with LVLs (9 with SCC, 6 with IN, and 10 with hyperplasia) were included. A targeted sequence was performed for LVLs and background mucosa using an esophageal cancer panel. Each mutation was checked whether it was oncogenic or not concerning OncoKB. In LVLs, TP53 was the most dominant mutation (80%). Furthermore, 72% of TP53 mutations was putative drivers. In background mucosa, NOTCH1 was the most dominant mutation (88%) and TP53 was the second most dominant mutation (48%). Furthermore, 73% of TP53 mutations and 8% of NOTCH1 mutations were putative drivers. Putative driver mutations of TP53 had significantly higher allele frequency (AF) in SCC than in IN and hyperplasia. Conversely, putative driver mutations of NOTCH1 did not have a significant accumulation of AF in the progression of carcinogenesis. Furthermore, in SCC, AF of TP53 mutations was significantly higher in LVLs than in background mucosa, but not in IN and hyperplasia. Regarding NOTCH1, a significant difference was not observed between LVLs and background mucosa in each group. The background mucosa in patients with LVLs already had putative driver mutations such as TP53 and NOTCH1 . Of these two genes, TP53 mutation could be the main target gene of carcinogenesis in esophageal SCC. Clinical Trials registry: UMIN000034247. Abstract : The background mucosa in patients with LVLs already has accumulated gene mutations. Notably, many putative driver mutations were confirmed in TP53 and NOTCH1. The TP53 could be the main target gene of the carcinogenesis in esophageal SCC; this mutation was also found in the background mucosa in high‐risk patients.